2011
DOI: 10.1016/j.ajhg.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the SPARC-Related Modular Calcium-Binding Protein 1 Gene, SMOC1, Cause Waardenburg Anophthalmia Syndrome

Abstract: Waardenburg anophthalmia syndrome, also known as microphthalmia with limb anomalies, ophthalmoacromelic syndrome, and anophthalmia-syndactyly, is a rare autosomal-recessive developmental disorder that has been mapped to 10p11.23. Here we show that this disease is heterogeneous by reporting on a consanguineous family, not linked to the 10p11.23 locus, whose two affected children have a homozygous mutation in SMOC1. Knockdown experiments of the zebrafish smoc1 revealed that smoc1 is important in eye development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…Recently, three groups used autozygosity/homozygosity mapping to narrow the locus for WAS to a 1–3 Mb interval at chromosome 14q24.2 [74, 76, 77]. All three researchers found mutations in the secreted protein acidic and rich in cysteine (SPARC)-related modular calcium binding 1 ( SMOC1 ) gene that were predicted to cause loss of function [74, 76, 77].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, three groups used autozygosity/homozygosity mapping to narrow the locus for WAS to a 1–3 Mb interval at chromosome 14q24.2 [74, 76, 77]. All three researchers found mutations in the secreted protein acidic and rich in cysteine (SPARC)-related modular calcium binding 1 ( SMOC1 ) gene that were predicted to cause loss of function [74, 76, 77].…”
Section: Introductionmentioning
confidence: 99%
“…All three researchers found mutations in the secreted protein acidic and rich in cysteine (SPARC)-related modular calcium binding 1 ( SMOC1 ) gene that were predicted to cause loss of function [74, 76, 77]. Mutations have so far been identified in 12 families, with evidence of genetic heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of anophthalmia and microphthalmia have been associated with homozygous and heterozygous mutations in genes at the core of forebrain regulatory networks (Beccari et al, 2013), such as the transcription factors (TFs) SOX2 (Fantes et al, 2003), OTX2 (Ragge et al, 2005), PAX6 (Glaser et al, 1994), VSX2 (CHX10) (Ferda Percin et al, 2000), RAX (Voronina et al, 2004), FOXE3 (Reis et al, 2010) and perhaps SIX6 (Gallardo et al, 2004); in key components of cell to cell communication, including SHH (Schimmenti et al, 2003) and BMP4 (Reis et al, 2011); or in genes involved in retinal progenitor proliferation and survival such as STRA6 (Pasutto et al, 2007;White et al, 2008), BCOR (Ng et al, 2004), HCCS (Indrieri et al, 2013;Morleo et al, 2005) and SMOC1 (Abouzeid et al, 2011;Okada et al, 2011). Yet, only a minor proportion of patients receive an accurate molecular diagnosis of the pathogenesis of their ocular malformation Williamson and FitzPatrick, 2014), indicating that additional causative genes need to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been implemented in two recent studies which identified homozygous mutations in SMOC1, encoding Sparc-related modular calcium-binding protein 1 (SMOC1), as a cause of the rare autosomal recessive Waardenburg anophthalmia syndrome (WAS) [83,84], a finding also reported in another study [85]. WAS is also known as ophthalmo-acromelic syndrome affecting development of the eyes (anophthalmia, microphthalmia) and limbs (post-axial oligodactyly, syndactyly).…”
Section: Mouse Models Generated By Insertional and Enu-induced Mutagementioning
confidence: 95%